THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ETHICS IN HIGHER EDUCATION AND STUDENT ACTIVITIES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This paper presents a comprehensive examination of how artificial intelligence (AI) influences ethical considerations within higher education and student life. It analyzes the effects of AI on academic honesty, educational practices, equal access to resources, data protection, and students’ professional futures. The study outlines both the advantages, such as increased efficiency and personalized learning, and the challenges, including dependency on technology, inequality, and risks of academic misconduct. The paper emphasizes the importance of establishing clear ethical standards and encouraging responsible AI usage in academic environments.